Demographic and socioeconomic determinants of adherence in digital patient-reported outcomes among patients with chronic diseases - Janis Nikkhah; Alessandro Campione; Viktoria Steinbeck; Laura Wittich; Christoph Pross; Reinhard Busse (npj Digital Medicine)
Abstract Engaging patients in the digital collection of electronic patient-reported outcome measures (ePROMs) and experience measures (ePREMs) is desirable for equitable, patient-centred chronic disease management; however, adherence remain unclear. This study examined demographic and socioeconomic determinants of adherence using ePROMs and ePREMs collected from patients with asthma, chronic obstructive pulmonary disease, diabetes, and coronary artery disease across Germany. Of the 200,338 patients invited to complete digital surveys, 4657 consented (initiation; 2.32%) and 2375 completed at least one ePROM (implementation; 51.00% of initiation). Initiation was highest among asthma patients (3.42%) and lowest among those aged ≥75 years (1.09%). Implementation followed an inverse U-shaped age pattern and was lowest among patients with diabetes and those with low or unreported income. Findings indicate barriers to adherence associated with demographic and socioeconomic factors. Strategies such as inclusive engagement, integration of surveys into clinical care, and clinical endorsement may improve adherence. Trial registration: drks.de; Identifier: DRKS00031656.